2013
DOI: 10.3109/10428194.2013.766731
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs in mantle cell lymphoma

Abstract: Mantle cell lymphoma (MCL) is a rare and aggressive subtype of non-Hodgkin lymphoma. New treatment modalities, including intensive induction regimens with immunochemotherapy and autologous stem cell transplant, have improved survival. However, many patients still relapse, and there is a need for novel therapeutic strategies. Recent progress has been made in the understanding of the role of microRNAs (miRNAs) in MCL. Comparisons of tumor samples from patients with MCL with their normal counterparts (naive B-cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 94 publications
1
10
0
Order By: Relevance
“…16,17 In the current study of two similar MCL trial cohorts, we find that the miR-18b expression level significantly adds prognostic information to the MIPI-B approach. By generating a new prognosticator, the MIPI-B-miR, we were able to predict survival of MCL patients after high-dose immunochemotherapy and ASCT and improve the gold standard prognosticator MIPI-B.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…16,17 In the current study of two similar MCL trial cohorts, we find that the miR-18b expression level significantly adds prognostic information to the MIPI-B approach. By generating a new prognosticator, the MIPI-B-miR, we were able to predict survival of MCL patients after high-dose immunochemotherapy and ASCT and improve the gold standard prognosticator MIPI-B.…”
Section: Discussionmentioning
confidence: 79%
“…The prognostic impact of miRNAs have previously been studied in MCL, but mainly in smaller, heterogeneous cohorts, treated by variant regimens 16,17 These studies have suggested a number of prognostic miRNAs including miR-18b, 29 and the entire miR-17~92a cluster. However, no other study identified miR-92a as a key component.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5 A number of studies have subsequently revealed the biological and clinical relevance of different miRNAs in various types of cancer, including CLL and the clinically more aggressive mantle cell lymphoma (MCL). [6][7][8][9][10][11] One of these miRNAs, miR26A1, was reported to be deregulated in several cancer types, such as thyroid anaplastic carcinoma, Burkitt lymphoma, and rhabdomyosarcoma, and was proposed to function as a tumor suppressor miRNA. [12][13][14] miR26A1 is known to be involved in several key signaling pathways (e.g., p53, TGF-b signaling) and to regulate several transformation-related targets, such as SMAD1 15 and EZH2.…”
Section: Introductionmentioning
confidence: 99%